The Gloves as Effective Personal Protective Equipment (PPE) of Indonesian Batik Workers - Cita Rosita Sigit Prakoeswa; Damayanti; Sylvia Anggraeni; Menul Ayu Umborowati; Sri Awalia Febriana (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Batik substances may increase the risk of biological function disruption to batik workers.Objective: To Determine the effectiveness of using test gloves in transepidermal water loss (TEWL), skinhydration level, and skin acidity (pH).Methods: This study was one group pretest-posttest design of 16 batik workers. Subjects use test glovesmade from neoprene on right hands and personal gloves made from thermoplastic polymer of vinyl chlorideon left hands in first and second week. Washed out for 2 weeks, last 2 weeks use test gloves on left handand personal gloves on right hand. TEWL, skin hydration level, and pH was examined by Cutometer dualMP-580Result: First and second week using test gloves on the right hand, significantly differences of TEWL levelon extensor and dorsum manus; skin hydration level on flexor, extensor, palmar, and dorsum manus; pHon extensor, palmar and dorsum manus (p<0.05; CI 95%). Fifth and sixth week using test gloves in theleft hand, significantly difference of TEWL level on dorsum manus, all area of skin hydration level and pHresults (p<0.05; CI 95%). No significant differences of comparison right and left hand in the first, second,fifth, and sixth week, that showed any types of gloves can protect batik workers from skin barrier disruption.Conclusion: Personal gloves and test gloves usage for protection doesn’t have much significant difference.Wearing gloves may also give risk to trigger contact dermatitis if not used properly or using incompatiblematerial.